2010
DOI: 10.17129/botsci.2318
|View full text |Cite
|
Sign up to set email alerts
|

¿Hay asincronía demográfica entre poblaciones locales de Tillandsia recurvata ? evidencias de su funcionamiento metapoblacional

Abstract: We studied the demography of nine populations of the epiphyte <em>Tillandsia recurvata</em> established on <em>Prosopis laevigata</em> in the Tehuacán region, in the Mexican state of Puebla, to evaluate whether they show demographic asynchrony, a basic condition for metapopulation persistence. These populations differed in the size of the occupied tree (volume of tree crown) and in their number of individuals. Two Lefkovitch matrices were built per population, one for 2001-2 and another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
1
7
0
3
Order By: Relevance
“…A survey by Mondragón et al (2015) revealed that nearly two-thirds of epiphytic orchid populations had l values !1.0. Furthermore, they found, as we did, that populations tend to function independently and asynchronously, a phenomenon that characterizes metapopulation dynamics (Tremblay et al 2006;Laube and Zotz 2007;Valverde and Bernal 2010). Thus, finding populations with negative growth rates may be normal and not necessarily cause for alarm.…”
supporting
confidence: 73%
“…A survey by Mondragón et al (2015) revealed that nearly two-thirds of epiphytic orchid populations had l values !1.0. Furthermore, they found, as we did, that populations tend to function independently and asynchronously, a phenomenon that characterizes metapopulation dynamics (Tremblay et al 2006;Laube and Zotz 2007;Valverde and Bernal 2010). Thus, finding populations with negative growth rates may be normal and not necessarily cause for alarm.…”
supporting
confidence: 73%
“…While none of the articles explicitly discusses the factors that might influence these phenophases, it is known that anemochorous plants in seasonal tropical forests tend to disperse their seeds during the dry season (de Lampe et al, 1992;Morellato and Leitão-Filho, 1996;Cortés-Flores et al, 2019) since this dispersal syndrome is closely linked to wind speed and the surrounding vegetation (Augspurger, 1986). Dispersal during the dry season results more effective given the lack of foliage, facilitating the flow of wind currents and allowing the seeds to be carried over longer distances (García-Franco and Rico-Gray, 1991;Mondragón and Calvo-Irabien, 2006;Valverde and Bernal, 2010;Escobedo-Sarti and Mondragón, 2016). As occurs with flowering, fructification, and seed dispersal are influenced by other phenological phases (Primack, 1987) because, for instance, successful regeneration of a species does not only depend on seed dispersal, but also on seeds being dispersed over favorable areas during periods that allow them to germinate and establish as seedlings (Clark et al, 1999).…”
Section: Factors That Determine Fruiting and Seed Dispersal Phenology In Vascular Epiphytesmentioning
confidence: 99%
“…Las poblaciones del género Tillandsia poseen un patrón de crecimiento en forma de bandas o agrupado, patrón que depende de la cercanía de la población a la costa, de la pendiente, de la cantidad de neblina a la que están expuestas, de la topografía del lugar (ya sea en zonas arenosas o rocosas, presente en colinas o a faldas de cerros) y del transporte aéreo de los sedimentos (Hesse, 2012). El crecimiento del género Tillandsia no se da de manera uniforme en toda el área, algunas zonas tienen mayor crecimiento y distribución que otras, tal como en el caso de T. recurvata, que posee variaciones en el crecimiento debido a la variabilidad de las CARBONO Y AGUA EN Tillandsia latifolia Enero -Julio 2020 ______________________________________________________________________________________ diferentes condiciones abióticas en las que se encuentra el área del tillandsial (por ejemplo, las diferencias en pendiente, sustrato, altura o intensidad y dirección de viento (Valverde & Bernal, 2010). Otro caso es el de Tillandsia latifolia Meyen, cuya densidad y distribución espacial tiene relación con la topografía y el sustrato en el que se encuentran, siendo la densidad de estas plantas mayor cuando se encuentran con exposición de neblina (Aponte & Flores, 2013).…”
Section: Introductionunclassified